Kr I spectra in the 5–14 µm range. (July 2020) - Civiš, S.; Kubelík, P.; Pastorek, A.; Zanozina, E.M.; Ferus, M.; Chernov, V.E.; Naskidashvili, A.V.; Zetkina, O.V.
Highlights: 105 new Kr I lines in the the 7002200 cm-1 range not observed previously. The 6 h, and 7 h, 7 i levels supported by ionization potential calculation. The updated system of Kr I level energies consistent to within 0.0019 cm -1. Graphical abstract: Abstract: Using the high-resolution time-resolved Fourier transform infrared spectroscopy of a plasma created in a positive column discharge cell, we record Kr I spectrum in the 700–7600 cm − 1 range. We report 88 new Kr I lines in the 700–2800 cm − 1 range previously not accessed by laboratory observations. This allows us to extract the excitation energies of the 6 h, and 7 h, 7 i levels of Kr I, which have not been measured before. We include these newly measured lines into the level optimisation together with the results of other high-resolution measurements to obtain an updated system of Kr I levels which is internally consistent to within 0.0019 cm − 1 .